Effects of letrozole on bone biomarkers and femur fracture in female rats - Yonden, Z.; Aydin, M.; Alcin, E.; Kelestemur, M. H.; Kutlu, S.; Yilmaz, B. (Servicio Publicaciones Universidad Navarra, 2009)
Z. YONDEN, M. AYDIN, E. ALCIN, M.H. KELESTEMUR, S. KUTLU and B. YILMAZ. Effects of letrozole on bone biomarkers and femur fracture in female rats. J Physiol Biochem, 65 (3), 267-276, 2009. We aimed to investigate the effects of the aromatase inhibitor letrozole on femur fracture and serum levels of alkaline phosphatase (ALP), calcium and phosphate in female rats. Intact 32 Sprague-Dawley female rats were divided into four groups (n=8): control, letrozole 0.2, letrozole 1 (treatment of 0.2 and 1 mg/kg for six weeks) and recovery (letrozole-treated 1 mg/kg for six weeks then allowed to recover for two weeks). Besides, 24 ovariectomized rats were divided into three groups (n=8): ovariectomized+control, ovariectomized+letrozole and ovariectomized+letrozole+ estradiol (10 mu g/rat). After experimental period, rats' femur bones were removed for biomechanical studies following decapitation. Serum ALP, calcium and phosphate were measured. Biomechanical values, ALP and phosphate significantly increased by letrozole in a dose-dependent manner (p<0.05) while calcium levels and net bone area decreased (p<0.05). Ultimate strength was positively correlated with ALP and phosphate and negatively correlated with calcium. The results indicate that letrozole may increase risk of bone fracture and affect bone biomarkers such as ALP, calcium and phosphate in both intact and ovariectomized rats.
Keywords: Letrozole; Biomechanics; Alkaline phosphatase; Calcium; Phosphate